English Proficiency of Secondary School Teachers in Indonesia - Lie, Anita; Tamah, Siti Mina; Trianawaty, Trianawaty; Triwidayati, Katarina Retno; Jemadi, Fransiskus (Beyond Words, 2019)
Responding to the growing need to foster communicative abilities in English, schools in Indonesia are driven to make their students proficient in English. However, the majority of English teachers themselves are still not prepared to use English as a means of communication; improving their English proficiency has thus become a matter of concern. As the first phase of a larger-scale study, this present study focuses on teachers’ English proficiency. Data for this study were collected from 149 secondary school teachers of English from five regions (Palembang, Yogyakarta-Sleman, Surabaya, Ruteng, and Maluku). They were asked to self-assess their English proficiencies based on the ACTFL (American Council on the Teaching of Foreign Languages) guidelines as well as to do an English Proficiency assessment. Fifty-two of these participants were teachers who were completing an in-service professional education program in Surabaya. The teachers assessed their proficiencies in interpersonal communication, presentational speaking, presentational writing, interpretive listening, and interpretive reading. The English Proficiency assessment includes syllabus-oriented items, General English items, and an essay. The study also conducted in-depth interviews of selected teachers. This study found that there is a gap between the teachers’ perception of their communicative abilities in English and their actual English proficiency.